Kepatuhan dan asertivitas pegawai negeri sipil pada penerapan peraturan daerah kawasan tanpa rokok: studi komparasi di Kabupaten Sleman dan Kabupaten Kulon Progo - Israini Susanti; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2017)
Civil servant compliance and assertiveness to non-smoking areas regulation: a comparative study in Sleman and Kulon Progo RegenciesPurpose:his study aimed to determine the differences of compliance and civil servants on the application of non-smoking areas in Sleman and Kulon Progo.MethodsThis analytical survey study used a cross-sectional approach. The subjects of this research were civil servants in the regional work units of Kulon Progo Regency as many as 1,072 and Sleman as many as 2,300 employees at 26 SKPD in Sleman and 25 SKPD in Kulon Progo. The sampling technique used multistage random sampling. The research instruments used were questionnaires, observations, and interviews to support the research. The analysis used was independent t-test and Mann-Whitney tests, namely to determine whether there was a relationship between independent and dependent variables.ResultsThis study found a difference of knowledge on application of perda KTR with (p = 0.000), attitude with (p = 0.003) and there was difference of socialization to applying of regulation of non-smoking area (p = 0.000). Logistic regression tests showed that the dominant factor of the non-smoking area law was the knowledge.ConclusionThere was a difference of knowledge, attitude, and socialization among civil servants in Kulon Progo and Sleman. There was no significant difference in attitude, smoking status, compliance, assertiveness, accessibility and social environment among civil servants in Kulon Progo and Sleman districts. The dominant factor affecting the compliance and assertiveness of civil servants is knowledge.